2018
DOI: 10.1007/s00214-018-2339-4
|View full text |Cite
|
Sign up to set email alerts
|

A density functional theory study of reactions of relevance to catalytic hydrocarbon synthesis and combustion

Abstract: Synthesis and combustion of hydrocarbons on a series of metal surfaces (Ag, Au, Al, Cu, Rh, Pt and Pd) were investigated using density functional theory (DFT). The adsorption energies for all species involved in these reactions, as well as the reaction energies and activation barriers on these surfaces, were calculated using the same models and DFT methods. The results were used to test the validity of the Brønsted-Evans-Polanyi (BEP) and transition state scaling (TSS) relationships for these reactions on thes… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2020
2020
2021
2021

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 71 publications
0
2
0
Order By: Relevance
“…The Brønsted–Evans–Polanyi (BEP) relation was also applied to the scaling, but this approach was found to be much weaker than both transition-state scalings, showing R 2 values of 0.19, 0.01, 0.87, and 0.88, respectively. Although the transition-state scaling was not necessarily stronger than the BEP relation 12 , previous studies have shown that the transition-state energies of particular surface reactions, such as hydrocarbon combustion and formation at high temperatures, are more suitably estimated by transition-state scaling 13 , 14 . According to Hammond’s postulate 15 , we can speculate that the transition states are structurally more similar to the initial states than to the final states.…”
Section: Resultsmentioning
confidence: 92%
“…The Brønsted–Evans–Polanyi (BEP) relation was also applied to the scaling, but this approach was found to be much weaker than both transition-state scalings, showing R 2 values of 0.19, 0.01, 0.87, and 0.88, respectively. Although the transition-state scaling was not necessarily stronger than the BEP relation 12 , previous studies have shown that the transition-state energies of particular surface reactions, such as hydrocarbon combustion and formation at high temperatures, are more suitably estimated by transition-state scaling 13 , 14 . According to Hammond’s postulate 15 , we can speculate that the transition states are structurally more similar to the initial states than to the final states.…”
Section: Resultsmentioning
confidence: 92%
“…Calculated negative adsorption energies indicate stabilization and an exothermic adsorption process. 89,90 The lower the negative energy, the stronger the adsorption between the adsorbate and substrate. On the basis of the increase in the anodic peak current observed at E pa = +0.3 V in Figure 3 (ii) of our nanocomposite, the presence of the aptamer greatly contributes to its stabilization.…”
Section: Computational Methodologymentioning
confidence: 99%